Case Report: A rare case of CD20-positive T-cell large granular lymphocyte leukemia with renal cell carcinoma: a challenging diagnosis - Jin, Yingming; Ren, Fupeng; Wang, Shuyan; Xu, Jin; Wu, Yingying; Tang, Jinfen; Xu, Jianfen (Frontiers in Hematology, 2023)
Large granular lymphocytic leukemia (LGLL) is a clonal lymphoproliferative disease with a slow course and considerable difficulties in the correct diagnosis and therapy. T-LGLL is the most prevalent subtype of LGLL, accounting for approximately 85%. T-LGLL co-existence with solid malignancies is relatively rare. CD20-positive T-cell neoplasm is a rare disease in clinics. In this case study, we report CD20-positive T-LGLL with renal cell carcinoma (RCC) that was eventually diagnosed by splenectomy and nephrectomy. The accumulation of cases will contribute to diagnose and treat CD20-positive T-LGLL complicated with solid tumors.